Electric impulse spring-assisted contact separation mode triboelectric nanogenerator fabricated from polyaniline emeraldine salt and woven carbon fibers. (November 2018) - Cheedarala, Ravi Kumar; Parvez, Abu Naushad; Ahn, Kyoung Kwan
Abstract: In this article, we used modified woven carbon fiber mat (wCF-COOH), as one of the contact-electrification Triboelectric Nanogenerator (TENG) friction layer to generate high open circuit voltage (V oc ) and short circuit current (I sc ). We designed the contact-separation mode TENG which is functional using spring structure. The oxidation of wCF into wCF-COOH by Piranha solution followed by coupling of aniline through electrostatic interactions and in-situ oxidative polymerization to get woven carbon fiber-polyaniline emeraldine salt (wCF.PANI.ES) composite is a novel approach. The wCF-PANI.ES composite displays the surface resistivity of 0.324 Ω m and serves as a friction layer to generate charges by harvesting energy through vertical contact-separation mode TENG against PVDF membrane. The dynamic interactions of novel wCF-PANI.ES and PVDF membrane produced high V oc of 95 V, and I sc of 180 μA, respectively. In particular, wCF-PANI.ES-TENG has shown an enhancement of 498% of V oc with respect to wCF-COOH-TENG due to availability of PANI layer. In addition, it was observed that the proposed wCF-PANI.ES-TENG has shown the output power of 12.4 mW at 5 Hz, and the rectified current upto 180 μA. The novel wCF-PANI.ES is the potential candidate for fulfilling the need of optimized energy harvesting device as an alternate material option for contact-separation mode TENGs. Graphical abstract: fx1 Highlights: wCF-PANI.ES and PVDF based contact-separation mode spring assisted TENG was developed. wCF-COOH was generated from neat wCF cloth using Piranha solution followed by coupling of aniline by electrostatically and then in-situ oxidation polymerization produced the wCF-PANI.ES composite. High triboelectric (V oc ) and (J sc ) were attained from wCF-PANI.ES-TENG, in particular, 95 V and 180 µA at 5 Hz, respectively. The proposed wCF-PANI.ES-TENG has shown the output power of 12.4 mW at 5 Hz, and the rectified current upto 180 μA.